Scaffolding Academic Writing for First-Year EFL University Students: A PRISMA-Guided Systematic Review and Thematic Synthesis - Vike Aprilianin Marwintaria Saputri (Journal of Adaptive Education, 2026)
Background: First-year EFL university students frequently encounter significant challenges in developing writing skills, necessitating effective instructional support. Although extensive research exists, gaps persist in understanding the impact of scaffolding strategies on writing abilities in higher education. Objective: This systematic review investigates scaffolding strategies for enhancing writing skills among first-year EFL students, focusing on (1) definitions and theoretical foundations, (2) strategies that improve writing ability, and (3) perceived challenges and benefits from both educators' and students' perspectives. Method: A systematic literature review was conducted in accordance with PRISMA guidelines across Scopus, ERIC, Web of Science, ProQuest, and Google Scholar (2019–2024). The search utilized keywords such as "scaffolding strategy," "teaching writing," and "writing ability." Of 1,148 initial records, 60 studies met the inclusion criteria after rigorous screening. Data were analyzed through thematic synthesis, and study quality was evaluated using the Mixed Methods Appraisal Tool (MMAT). Results: Scaffolding strategies were identified across various writing stages: post-writing revising (80.0%), while-writing drafting (78.3%), pre-writing planning (68.3%), and editing and proofreading (48.3%). Five categories of scaffolding emerged: instructional, peer, technological, metacognitive, and affective. Major challenges included diverse proficiency levels (72%), limited instructional time (65%), balancing scaffolding with learner autonomy (58%), and restricted vocabulary (60%). Reported benefits comprised improved writing quality (80%), enhanced learner autonomy (75%), increased motivation (70%), and more effective peer learning (65%). Conclusion: Scaffolding is a critical component of EFL writing instruction, with its effectiveness contingent upon teachers' ability to tailor strategies to student proficiency and integrate multiple scaffolding types. Limitations of this review include a focus on English-language publications and the exclusion of unpublished dissertations. Future research should employ longitudinal and experimental designs, explore digital scaffolding tools, and investigate differentiated strategies across varying proficiency levels.